Upaya Meningkatkan Keterampilan Membaca melalui Penggunaan Media Gambar pada Siswa Kelas II SDN 1 Kebon Jeruk Bandar Lampung Tahun Pelajaran 2022/2023 - Isna Eliyani; Surastina Surastina; Hendra Saputra (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2023)
The problem in this study is the low learning outcomes of Indonesian language in reading skills of grade II students of SD Negeri 1 Kebon Jeruk Bandar Lampung. The purpose of this study was to improve the reading skills of grade II students of SD Negeri 1 Kebon Jeruk and to see students' activities in reading skills through the use of picture media. The type of research used is Classroom Action Research (PTK) with the stages of each cycle consisting of: planning, implementation, observation, and reflection. The research subjects consisted of 26 students of which 12 male students and 14 female students. The data collection tools used were observation sheets, documentation and oral reading tests. Data analysis techniques are qualitative data analysis and quantitative data analysis. The results of the research on reading skills using gambat media were able to improve students' reading skills. It is evident that the improvement of reading skills using image media in cycle I with an average of 67.73% or 57.69% of students who meet the value of the completeness criteria, and in cycle II experienced a good improvement by using image media with an average of 80.76% or 84.61% of students who met the minimum completion criteria (KKM). In addition, the results of observations of student and teacher activities in learning to read from cycle I to cycle II have increased, this shows that the use of image media can improve students' reading skills.